Lepton Flavor Violation in Economical 3-3-1 Model with Neutrino Singlets - Hue, Le Tho; Khoi, Dinh Phan; Phuong, Hoang Hanh; Hung, Ha Thanh (Communications in Physics, 2019)
Lepton flavor violating (LFV) decays of charged leptons \(μ→ eγ\) and SM-like Higgs boson \(h→ μτ\) are discussed in the framework of the economical 3-3-1 model adding three additional singlets neutrinos (E331\(X_R\)). We will show that the appearance of new neutrinos and charged Higgs bosons in this model can result in interesting regions of the parameter space, which satisfy the recent experimental bound of \(Br(μ→ eγ)\) as well as give large \(Br(h→ μτ)≥ \mathcal{O}(10^{-7})\) . In these regions, the charged Higgs boson mass lies within the range of \(2-3\) TeV. Our results show that the LFV decays are important channels to distinguish the E331\(X_R\) and the original economical (E331) models, which predicts suppressed LFV decay rates